2023
DOI: 10.3390/gels9020168
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Low-Temperature Rheology of Polar Drilling Fluid and Its Regulation Method

Abstract: Drilling fluid is the blood of drilling engineering. In the polar drilling process, the ultra-low temperature environment puts high demands on the rheological performance of drilling fluids. In this paper, the effects of temperature, ice debris concentration and weighting agent on the rheological properties of drilling fluids were studied. It was found that the lower the temperature and the higher the ice debris concentration, the higher the drilling fluid viscosity, but when the ice debris concentration was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The gelation of polymer is affected by temperature. 42 In order to evaluate the feasibility of TPGS 1000 as the thermosensitive gel carrier, the effect of temperature on gelation of TPGS 1000 was studied and the results are illustrated in Table 3. The results showed that all the samples could gel within 5 min, and GT decreased from 5 min to 2 min 30 s as the temperature increased from 35 to 38 C. Meanwhile, we found that the viscosity of the sample only increased at 34 C, but it could not gel even if it was extended to 10 min.…”
Section: The Effect Of Temperature On Gelationmentioning
confidence: 99%
“…The gelation of polymer is affected by temperature. 42 In order to evaluate the feasibility of TPGS 1000 as the thermosensitive gel carrier, the effect of temperature on gelation of TPGS 1000 was studied and the results are illustrated in Table 3. The results showed that all the samples could gel within 5 min, and GT decreased from 5 min to 2 min 30 s as the temperature increased from 35 to 38 C. Meanwhile, we found that the viscosity of the sample only increased at 34 C, but it could not gel even if it was extended to 10 min.…”
Section: The Effect Of Temperature On Gelationmentioning
confidence: 99%
“…To significantly raise drilling process efficiency, it is important to study the rheological performance of drilling fluid. It plays a key role in successful drilling operations, downhole safety, and improving drilling speed [2].Water based drilling fluid (Water bentonite suspensions) is one of two main classes of drilling fluids used in drilling. They have a variety of applications in drilling, particularly in offshore drilling sites, because of their robust colloidal characteristics and ability to raise liquid viscosity [3].…”
mentioning
confidence: 99%
“…To significantly raise drilling process efficiency, it is important to study the rheological performance of drilling fluid. It plays a key role in successful drilling operations, downhole safety, and improving drilling speed [2].…”
mentioning
confidence: 99%